Fates of Setaria faberi and Abutilon theophrasti seeds in three crop rotation systems. (2nd January 2014) - Liebman, M; Miller, Z J; Williams, C L; Westerman, P R; Dixon, P M; Heggenstaller, A; Davis, A S; Menalled, F D; Sundberg, D N; Lutman, Peter
Summary Weed seeds in and on the soil are the primary cause of weed infestations in arable fields. Previous studies have documented reductions in weed seedbanks due to cropping system diversification through extended rotation sequences, but the impacts of different rotation systems on additions to and losses from weed seedbanks remain poorly understood. We conducted an experiment in Iowa, USA, to determine the fates of Setaria faberi and Abutilon theophrasti seeds in 2‐, 3‐ and 4‐year crop rotation systems when seed additions to the soil seedbank were restricted to a single pulse at the initiation of the study. Over the course of the experiment, seedlings were removed as they emerged and prevented from producing new seeds. After 41 months, seed population densities dropped >85% for S. faberi and >65% for A. theophrasti, but differences between rotation systems in the magnitude of seedbank reductions were not detected. Most of the reductions in seedbank densities took place from autumn through early spring in the first 5 months following seed deposition, before seedling emergence occurred, suggesting that seed predation and/or seed decay was important. For S. faberi, total cumulative seedling emergence and total seed mortality did not differ between rotation systems. In contrast, for A. theophrasti, seedling emergence was 71% lower and seed mortality was 83% greater in the 3‐ and 4‐year rotation systems than in the 2‐year system. Results of this study indicate that for certain weed species, such as A. theophrasti, crop rotation systems can strongly affect life‐history processes associated with soil seedbanks.